The Little Data Book 2013 - World Bank (Washington, DC, 2013)
The Little Data Book 2013 is a pocket edition of World Development Indicators 2013. It is intended as a quick reference for users of the World Development Indicators database, book, and mobile app. The database, which covers more than 1,200 indicators and spans more than 50 years